Morphological Study of Coelastrum cambricum from the Peat Water of Palangka Raya, Indonesia - Chaidir Adam; Agus Haryono (Nusantara Science and Technology Proceedings, 2022)
Coelastrum Nägeli 1849 is a genus of microalgae belonging to the scenedesmaceae family and currently has 31 taxonomically accepted species. Coelastrum can be found in the freshwater environment, e.g., in ditches, ponds, lakes, and swamps forming small colonies called coenobia. As no data records the description of this genus from the peat water environment, it is necessary to conduct a morphological study, especially the Coelastrum cambricum species which is commonly found in peat waters. Water samples were collected from peat waters in a ditch at the Bukit Keminting Road (Palangka Raya) near the Fisheries Department, University of Palangka Raya. Morphological examination of Coelastrum cambricum was carried out microscopically directly on the collected water samples and then photographed for further identification. Coelastrum cambricum was identified from the water samples collected from peat water at the sampling site. The peat water has a brownish color and looks fairly clear like brewed tea that allows enough sunlight to penetrate it. C. cambricum forming a spherical coenobium consisting of 4-32 cells and appear green in color and it is observed that coenobium groups form larger colonies consisting of 4 to 24 coenobia. The diameter of coenobia ranges from 40-62?m. In this study also observed the distinctive morphological characteristics of C. cambricum where 6 cells were observed in the center of the coenobium forming a pentagonal pattern that looked the same in all specimens observed. This characteristic has the potential to be studied further as a key feature of Coelastrum species identification.